Studi italiani di linguistica slava Strutture, uso e acquisizione - BONOLA, Anna Paola; COTTA RAMUSINO, PAOLA MARIA; GOLETIANI, LIANA (Biblioteca di Studi Slavistici, 2014)
The essays published here document the most recent linguistic research carried out in the field of Italian Slavistics. The contributions collected in the first part of the volume analyze the morphological and syntactic structures of various Slavic languages; the second part is dedicated to linguistic use; the last contains three experimental studies on the acquisition of Slavic languages, a particularly promising research area both for glottodidactic applications and for the contribution to studies on the relationship between thought and language. There are several Slavic languages studied (Czech, Polish, Russian, Slovenian, Ukrainian dialects, southern Slavic languages, including the spoken languages of the Pomaks in the Rhodope mountains), different perspectives (diachronic and synchronic) and various methodological approaches, testifying to the richness and progressive maturation of linguistic studies within Italian Slavistics.